Down-Regulation of a Nicotinate Phosphoribosyltransferase Gene, OsNaPRT1, Leads to Withered Leaf Tips . Issue 2 (5th April 2016) - Wu, Liwen; Ren, Deyong; Hu, Shikai; Li, Gengmi; Dong, Guojun; Jiang, Liang; Hu, Xingming; Ye, Weijun; Cui, Yongtao; Zhu, Li; Hu, Jiang; Zhang, Guangheng; et al.
Abstract : Defects in a NAD salvage pathway trigger the accumulation of nicotinamide and increase histone H3K9 acetylation and expression of senescence-related genes in rice. Abstract: Premature leaf senescence affects plant growth and yield in rice. NAD plays critical roles in cellular redox reactions and remains at a sufficient level in the cell to prevent cell death. Although numerous factors affecting leaf senescence have been identified, few involving NAD biosynthetic pathways have been described for plants. Here, we report the cloning and characterization of Leaf Tip Senescence 1 ( LTS1 ) in rice ( Oryza sativa ), a recessive mutation in the gene encoding O. sativa nicotinate phosphoribosyltransferase (OsNaPRT1) in the NAD salvage pathway. A point mutation in OsNaPRT1 leads to dwarfism and the withered leaf tip phenotype, and the lts1 mutant displays early leaf senescence compared to the wild type. Leaf nicotinate and nicotinamide contents are elevated in lts1, while NAD levels are reduced. Leaf tissue of lts1 exhibited significant DNA fragmentation and H2 O2 accumulation, along with up-regulation of genes associated with senescence. The lts1 mutant also showed reduced expression of SIR2-like genes ( OsSRT1 and OsSRT2 ) and increased acetylation of histone H3K9. Down-regulation of OsSRTs induced histone H3K9 acetylation of senescence-related genes. These results suggest that deficiency in the NAD salvage pathway can trigger premature leaf senescence due to transcriptional activation of senescence-related genes.